Pertanggung Jawaban Hukum Bagi Notaris Atas Tindak Pidana Yang Dilakukan Oleh Karyawan Notaris - Mayrsha Ayu Khairina (Officium Notarium, 2021)
This study aims to analyze and identify the form of the notary's responsibility as a leader against criminal acts committed by the notary’s employees? and the legal protection of a notary against criminal acts committed by notary employees? This is a normative research, supported by primary data in the form of Law Number 2 of 2014 concerning Notary Positions and related court decisions as well as secondary data in the form of integrated interviews with sources from practitioners and academics. The approach taken by the author is a legal approach and a case approach which is described in a qualitative descriptive manner. The results of this research conclude that firstly, if a notary’s employee commits a criminal act of forging a letter which results in a defect in the authentic deed or a loss for a third party, then it is possible that the notary can be held responsible for this as in the crime of participation contained in Article 55 Jo. Article 263 paragraphs (1) and (2) of the Criminal Code. Second, there are forms of legal protection provided by the law, namely from the Notary Honorary Council and self-protection.Keywords: Forgery of letter; notary’s employee; notary responsibilityAbstrakPenelitian ini bertujuan untuk menganalisis dan mengetahui bagaimana bentuk pertanggungjawaban notaris sebagai pimpinan terhadap tindak pidana yang dilakukan oleh karyawan notaris? serta bagaimanakah perlindungan hukum notaris atas tindak pidana yang dilakukan oleh karyawan notaris? Penelitian ini adalah penelitian normatif. Didukung dengan data primer yang berupa Undang-Undang Nomor 2 Tahun 2014 tentang Jabatan Notaris dan putusan pengadilan terkait serta data sekunder berupa wawancara terpadu dengan narasumber yang berasal dari praktisi dan akademisi. Pendekatan yang dilakukan oleh penulis ialah dengan pendekatan undang-undang (statue approach) dan pendekatan kasus yang dijelaskan secara deskriptif kualitatif. Hasil penelitian ini menyimpulkan, pertama, bilamana karyawan notaris melakukan tindak pidana pemalsuan surat yang mengakibatkan cacatnya akta otentik atau kerugian bagi pihak ketiga, maka tidak menutup kemungkinan notaris dapat dipertanggungjawabakan atas hal tersebut sebagaimana dalam tindak pidana penyertaan yang termuat dalam Pasal 55 Jo. Pasal 263 ayat (1) dan (2) KUHP. Kedua, bentuk perlindungan hukum yang diberikan oleh Undang-Undang, yakni dari Majelis Kehormatan Notaris dan perlindungan diri sendiri.Kata Kunci: Pekerja notaris; pemalsuan surat; pertanggungjawaban notarisForgery of letter; notary’s employee; notary responsibility